Bibliography of literature on First Peter - Casurella, Anthony. (New Testament tools and studies, 1996)
The Bibliography of Literature on First Peter gives comprehensive publication details of a categorized list of articles and books concerned with the exposition of the New Testament letter known as 1 Peter. The bibliography, which primarily presents works of modern scholarship but also includes important works which have appeared throughout the lengthy period of Christian interpretation, has been conceived with the needs of a variety of users in mind. It provides an extremely valuable reference tool for all those interested in a deeper understanding of this important document of early Christianity, and will meet the needs of researchers of all kinds, from lay students to the professional scholar. Not every work represented in this bibliography will be of equal use to all; but judicious selection on the basis of the helpful classification provided will save the researcher much time.